2018
DOI: 10.25135/rnp.34.17.09.160
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents Isolated from Lycium shawii and their Chemotaxonomic Significance

Abstract: Phytochemical investigation of Lycium shawii Roem. & Schult provided fourteen compounds, including lyciumate (1), dehydrocostus lactone (2), costunolide (3), catechin (4), lyciumaside (5), emodin (6), (11), nonacosane-10-ol (12), betulinic acid (13) and β-sitosterol glucopyranoside (14). The compounds may be classified as three sesquiterpene lactones (1-3), two phenolic compounds (4 and 5), six anthraquinones (6-11), one long chain alcohol (12), one lupane-type triterpenoid (13) and a steroid (14). Compounds 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In line with the study of Hussain et al (2010) andBrito et al (2014), MS/MS spectra of S. tomentosa and S. condensata at m/z 299 and 313 with the neutral loss of methyl ether were attributed to diosmetin and luteolin-dimethyl ether (Table 2). As shown in previously published works, luteolin-methyl ether was characterized in Phlomis cashmeriana Royle ex Benth.…”
Section: Discussionsupporting
confidence: 76%
“…In line with the study of Hussain et al (2010) andBrito et al (2014), MS/MS spectra of S. tomentosa and S. condensata at m/z 299 and 313 with the neutral loss of methyl ether were attributed to diosmetin and luteolin-dimethyl ether (Table 2). As shown in previously published works, luteolin-methyl ether was characterized in Phlomis cashmeriana Royle ex Benth.…”
Section: Discussionsupporting
confidence: 76%
“…The molecular features were extracted by screening the detected nodes at various retention times per minute, with a minimum intensity of 6,000 counts, and aligned with previously detected compounds considering adducts ([M + H] + , [M+2H] + , and [M-H] - ). The identified derivative metabolites were (peak A) P-coumaric acid (4-hydroxycinnamic acid) ( Pei et al, 2016 ); (peak B) aloe-emodin ( Rehman et al, 2018 ); (peak C) oxalic acid isobutyl pentyl ester (2-methylpropyl pentyl ethanedioate) ( Singariya et al, 2015 ); (peak D) di-n-octyl phthalate (dioctyl 1,2 benzenedicarboxylate) ( DeAngelo et al, 1986 ); (peak E) apigenin (4,5,6-trihydroxy flavone) ( Shukla and Gupta, 2010 ); (peak F) chrysophanol-8-O-β-D-glucoside ( Rehman et al, 2016 ); (peak G) nonacosan-10-ol, ( Yao et al, 2011 ); (peak H) lyciumate ( Rehman et al, 2019 ); and (peak I) betulinic acid ( Yao et al, 2011 ), and means m/z implies measured m/z.…”
Section: Resultsmentioning
confidence: 99%
“… Base peak chromatograms of the L. shawii methanolic extract were extracted, and tentatively identified secondary metabolites are as follows: P-coumaric acid (4-hydroxycinnamic acid) ( Pei et al, 2016 ) (A), aloe-emodin ( Rehman et al, 2018 ) (B), oxalic acid isobutyl pentyl ester (2-methylpropyl pentyl ethanedioate) ( Singariya et al, 2015 ) (C), di-n-octyl phthalate (dioctyl 1,2 benzenedicarboxylate) ( DeAngelo et al, 1986 ) (D) , apigenin (4,5,6-trihydroxy flavone) ( Shukla and Gupta, 2010 ) (E) , chrysophanol-8-O-β-D-glucoside ( Rehman et al, 2016 ) (F) , nonacosan-10-ol ( Yao et al, 2011 ) (G) , lyciumate ( Rehman et al, 2019 ) (H) , betulinic acid ( Yao et al, 2011 ) (I) , and m/z implies measured m/z . …”
Section: Resultsmentioning
confidence: 99%
“…Lyciumate, cyclopentapyrrolidine, imidazole, piperidine, nortropane, tropane, pyrrole, spermine, costunolide, catechin, lyciumaside, emodin, betulinic acid, β-sitosterol glucopyranoside, quercetin, gallic acid, rutin, ρ-coumaric acid, ferulic acid [177,178] Reported data revealed that LD 50 of the L. shawii extract was greater than 2000 mg/kg b.w in animal model [179].…”
Section: Lycium Shawiimentioning
confidence: 99%